COPYRIGHT LAW AND TEXT AND DATA MINING - Ivanović, Svjetlana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Digital environment poses new challenges to the traditional concept of copyright protection. Digital copies of works, new forms of exploitation of protected subject matter, the impossibility of adequate enforcement of intellectual property rights on the Internet and, in this regard, the reexamination of the role of intermediaries, are just some of the issues that have occupied the scientific and professional public. New circumstances necessarily impose changes in the copyright protection regime and the introduction of new rights, but also new exceptions and limitations on copyright. Directive on copyright and related rights in the Digital Single Market introduced in EU legislation exceptions for text and data mining. In the digital environment, in conditions when we have large amount of data, an analytical technique is used, more precisely text and data collection and processing, aimed at finding correlations and patterns, and extracting information from large amount of data, using automated technique. Text and data mining may be performed in variety of fields and for different purposes, for scientific research, research in journalism, medicine, business or for market research purposes. The text and data may be protected by copyright and then the question of possible infringement of rights is raised. For this reason, the new Directive introduced two mandatory exceptions on copyright and related rights for the purpose of text and data mining, one of which is explicitly provided for the purposes of scientific research. The exceptions are important for the freedom of scientific research in the digital environment, but also for some issues related to the development of artificial intelligence.